The Theory and Demonstration of the Solid-Fluid Transformation of Ice Water - Yong-Yan Wang; Xi-Yan Fan; Nan Qin; Jian-Guang Li; Chuan-Qi Su (Advances in Mathematical Physics)
In this paper, a mathematical model for describing the solid-fluid transformation of ice water is put forward based on the special geometry cases. The correctness of the obtained model is verified through comparison with numerical analysis and experiments. The good agreement indicates that the obtained model is available for the study of the solid-fluid transformation of ice water. The theory derived in this paper lays a foundation for the research of solid-fluid transformation phenomena of other materials and may have important applications in engineering areas such as rheology, creep, and instability of materials.